Urban air pollution monitoring using scanning Lidar. (March 2020) - Xian, Jinhong; Sun, Dongsong; Xu, Wenjing; Han, Yuli; Zheng, Jun; Peng, Jiancao; Yang, Shaochen
Abstract: We have developed a scanning Lidar system in this work to detect urban air pollution changes in real time and locate the sources of urban air pollution. We first proposed an algorithm to retrieve atmospheric extinction coefficients, which we used to create Lidar maps. Using Lidar map of the average extinction coefficients, we identified the locations of the local maximum values, and hence, the positions of the urban air pollution sources. Experimental results indicate that this method is effective for urban air pollution monitoring. Graphical abstract: Image 1 Highlights: A new algorithm is proposed to retrieve atmospheric extinction coefficients. Ours is the first study to date that produces high-quality Lidar maps of atmospheric extinction coefficients. The sources of urban air pollution can be located by searching for the maximum values of the average extinction coefficient. The location of urban air pollution source is found for two cities in China.